Longitudinal assessment of airway responsiveness from 1 month to 18 years in the PIAF birth cohort - Cox, D.; Mullane, D.; Zhang, Guicheng; Turner, S.; Hayden, C.; Goldblatt, J.; Landau, L.; Le Souëf, P. (2015)
The Perth Infant Asthma Follow-up (PIAF) study involves a birth cohort of unselected subjects who have undergone longitudinal assessments of airway responsiveness at 1, 6 and 12 months and 6, 11 and 18 years of age. The aim of this study was to determine the relationship between increased airway responsiveness throughout childhood and asthma in early adult life. Airway responsiveness to histamine, assessed as a dose–response slope (DRS), and a respiratory questionnaire were completed at 1, 6 and 12 months and 6, 11 and 18 years of age. 253 children were initially recruited and studied. Airway responsiveness was assessed in 203, 174, 147, 103, 176 and 137 children at the above-mentioned time points, respectively (39 participants being assessed on all test occasions). Asthma at 18 years was associated with increased airway responsiveness at 6, 12 and 18 years, but not during infancy (slope 0.24, 95% CI 0.06–0.42; p=0.01; slope 0.25, 95% CI 0.08–0.49; p=0.006; and slope 0.56, 95% CI 0.29–0.83; p<0.001, respectively). Increased airway responsiveness and its association with asthma at age 18 years is established between infancy and 6 years. We propose that airway responsiveness in early life reflects the initial airway geometry and airway responsiveness later in childhood increasingly reflects immunological responses to environmental influences.